Eating and feeding behaviours in children in low‐income areas in Nairobi, Kenya. Issue 4 (31st May 2020) - Mutoro, Antonina N.; Garcia, Ada L.; Kimani‐Murage, Elizabeth W.; Wright, Charlotte M.
Abstract: Child eating and caregiver feeding behaviours are critical determinants of food intake, but they are poorly characterized in undernourished children. We aimed to describe how appetite, food refusal and force‐feeding vary between undernourished and healthy children aged 6–24 months in Nairobi and identify potential variables for use in a child eating behaviour scale for international use. This cross‐sectional study was conducted in seven clinics in low‐income areas of Nairobi. Healthy and undernourished children were quota sampled to recruit equal numbers of undernourished children (weight for age [WAZ] or weight for length [WLZ] Z scores ≤2SD) and healthy children (WAZ > 2SD). Using a structured interview schedule, questions reflecting child appetite, food refusal and caregiver feeding behaviours were rated using a 5‐point scale. Food refusal and force‐feeding variables were then combined to form scores and categorized into low, medium and high. In total, 407 child–caregiver pairs, aged median [interquartile range] 9.98 months [8.7 to 14.1], were recruited of whom 55% were undernourished. Undernourished children were less likely to 'love food' (undernourished 78%; healthy 90% p = < 0.001) and more likely to have high food refusal (18% vs. 3.3% p = <0.001), while their caregivers were more likely to use high force‐feeding (28% vs. 16% p = 0.03). Undernourished children in low‐income areas in Nairobi are harder to feed than healthy children, and force‐feeding is used widely. A range of discriminating variables could be used to measure child eating behaviour and assess the impact of interventions.